2023
DOI: 10.3390/ani13162556
|View full text |Cite
|
Sign up to set email alerts
|

Changes in S100A8/A9 and S100A12 and Their Comparison with Other Analytes in the Saliva of Pigs with Diarrhea Due to E. coli

Abstract: The family of calgranulins includes S100A8 (calgranulin A), S100A9 (calgranulin B), which can appear as a heterodimer known as S100A8/A9 or calprotectin, and S100A12 (calgranulin C). These proteins are related to different inflammatory conditions, immune-mediated diseases, and sepsis and are considered biomarkers of potential interest. This study aims to evaluate if S100A8/A9 and A12 could change in pigs with diarrhea due to E. coli and to compare the changes of S100A8/A9 and A12 with other analytes in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Salivary biomarker concentrations can be analyzed using different techniques. The most frequently used methods include antibody-based techniques like ELISA (enzyme-linked immunosorbent assay), TR-IFMA (Time-resolved immunofluorometric assay), and alphaLISA ® (Perkin Elmer, Malines, Belgium) [ 36 , 37 , 38 ], enzymatic assays for enzymes like α-amylase and adenosine deaminase [ 39 ], and proteomic approaches like HPLC, gel-based or liquid-based separation followed by MS/MS [ 40 ]. Although all these techniques have the same purpose, namely determining the quantity of a molecule in a biological sample, some variation in outcome between the different techniques is possible.…”
Section: The Salivary Proteomementioning
confidence: 99%
See 1 more Smart Citation
“…Salivary biomarker concentrations can be analyzed using different techniques. The most frequently used methods include antibody-based techniques like ELISA (enzyme-linked immunosorbent assay), TR-IFMA (Time-resolved immunofluorometric assay), and alphaLISA ® (Perkin Elmer, Malines, Belgium) [ 36 , 37 , 38 ], enzymatic assays for enzymes like α-amylase and adenosine deaminase [ 39 ], and proteomic approaches like HPLC, gel-based or liquid-based separation followed by MS/MS [ 40 ]. Although all these techniques have the same purpose, namely determining the quantity of a molecule in a biological sample, some variation in outcome between the different techniques is possible.…”
Section: The Salivary Proteomementioning
confidence: 99%
“…Additionally, discoloration of the sample may also impact spectrophotometric methods [ 41 , 55 , 56 ]. Some researchers report that sampling was postponed if animals ate or drank at the scheduled time since these acts might muddle the samples [ 38 ]. Oral rinsing before saliva collection therefore seems beneficial [ 55 ].…”
Section: The Salivary Proteomementioning
confidence: 99%
“…Ortin-Bustillo et al have shown that the levels of certain proteins such as S100A8/A9 and/or A12 are significantly increased in pigs with diarrhea infected by Escherichia coli. These proteins are typically associated with various inflammatory conditions, immune-mediated diseases, and sepsis, and are considered as potential and interesting biomarkers [8]. The activity levels of adenosine deaminase (ADA) are significantly elevated in the saliva of animals with localized inflammation, gastrointestinal diseases, and respiratory system diseases [9].…”
Section: Introductionmentioning
confidence: 99%